Celebrities on Social Networking Sites Advertisements and Their Impact on Purchase Decisions - Samadova, Aygun (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
[Abstract Not Available]
Master of Arts in Communication and Media Studies. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Communication, Dept. of Communication and Media Studies, 2016. Supervisor: Assoc. Prof. Dr. Agah Gümüş.
Keywords: Communication and Media Studies; Consumer behavior- Internet marketing - Social Networking Sites - Celebrities in Adevertisements; Electronic commerce - Psychological aspects; Social media - Marketing - Internet marketing - Social marketing; Social Networking Sites; Social Media; Advertising and Uses and Gratification Theory